PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE BANGUN KOTA NUMERASI BERBASIS ASSEMBLR EDU PADA MATERI PERKALIAN DI KELAS IV SD NEGERI 023908 BINJAI - M. Hafidz Al Rasyid; Elvi Mailani; Andri Kristianto (STKIP Subang, 2026)
This research aims to develop an Assemblr Edu-based Puzzle learning media on multiplication material for fourth-grade elementary school students that meets valid, practical, and effective criteria. The study employed Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). Data collection instruments included material and media validation sheets, practicality assessment sheets by teachers, and multiple-choice tests (pretest-posttest). The subjects were 32 fourth-grade students at SD Negeri 023908 Binjai. The results showed that material expert validation reached 88% (very feasible), media expert validation 91% (feasible with revision), and practicality by the teacher 95.53% (very practical). The effectiveness test using N-Gain obtained a score of 0.5759 (medium category) with a percentage of 57.59% (moderately effective). Students' average score increased from 59.375 (pretest) to 80.469 (posttest). Thus, the Assemblr Edu-based Puzzle learning media is declared feasible and effective for use in learning multiplication in grade IV elementary school.